Transient electromagnetic field radiated by grounding systems caused by lightning strike in a dissipative half-space. Issue 1 (1st January 2017) - Rouibah, T.; Bayadi, A.; Harid, N.; Kerroum, K.
Abstract: In this work, a method is proposed for the calculation of the electromagnetic field radiated by a grounding system in a semi-infinite dissipative medium subjected to a current excitation generated by the lightning strike. The assessment of the induced current distribution on the grounding system due to a transient excitation is obtained by solving Pocklington's equation using the method of moments. A new method for the calculation of the transient electromagnetic field following the injection of a lightning current or short circuit is also developed. This method is based on the concept of the hertzian dipoles and the asymptotic expansion of a single dipole. A MATLAB computer program has been developed for the determination of the induced currents. The program is validated by comparing its results with those obtained with the commercial software NEC 4.